25 EVALUATION OF NEUROPEPTIDE CONCENTRATIONS IN SERUM SAMPLES ANALYZED BY ENZYME-LINKED IMMUNOSORBENT ASSAY. (1st March 2006) - Goodwin, L. O.; Wang, X. P.; Goodwin, C.; Guzowski, D.; Gawel, C.; Chandrasekaran, A.; Mann-Finnerty, K.; Correll, C.
Abstract : Background: Clinical investigators are interested in elucidating the role of neuropeptides in diverse physiological processes. Neuropeptides act as integrative chemical messengers, from one discrete neuronal population to another. These molecules are also involved in coupling transductive events from neurons to immune cells regulating many biological functions, metabolism, and disease. Neuropeptide degradation is controlled by proteolytic enzymes and affected by disease states such as pain and analgesia, appetite control, inflammation, sepsis, mood, and affective behavior. Clarifying levels and pathways of circulating neuropeptides could drive the design of effective drugs to modulate the metabolic processes. Methods: We measured serum concentrations of nine different neuropeptides including NPY, AGRP, aMSH, MCH, CCK, CART, peptide YY(3-36), GLP, and Galanin by commercially available enzyme-linked immunosorbent assay (ELISA) kits (Pheonix Pharmaceuticals, Austin, TX). The peptide extraction method was essentially as recommended by the ELISA manufacturer. Micro BCA assay was used to measure total protein concentration. Results: The analysis of 9 neuropeptides from frozen serum samples (current GCRC study) by competitive ELISA were within the low range of the standard curve for each of the ELISAs (0.01-10 ng/mL). Considerable CV (coefficient of variability) in some duplicate samples was seen due to sensitivity of the ELISA or interference of abundant proteins within the serum samples. Thus, we analyzed the effect of peptide extraction of the serum samples. Different amounts (0-50 ng/mL) of peptideYY(3-36) was spiked into normal human serum to assess assay sensitivity. Spiked normal and four clinical sera samples were subjected to peptide extraction, and total protein and peptide YY(3-36) concentrations found for all paired extracted and nonextracted samples. There were no significant protein losses in the extracted samples as analyzed with BCA assay. However, there are significant reductions (Å50%) in peptide YY(3-36) concentrations in the four clinical serum samples that underwent peptide extraction. Peptide YY(3-36) neuropeptide may complex with bulky abundant proteins such as albumin. Removal of proteins from these serum samples did not yield higher sensitivity or improve CV, in the absence of concentrating the sera, which would reduce the sample volume and number. This work was supported by funds from the General Clinical Research Center, the Feinstein Institute for Medical Research at North Shore-LIJ Health System.